2007
DOI: 10.1007/s00167-007-0328-6
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of stability of autografts compared to allografts after anterior cruciate ligament reconstruction

Abstract: Allografts have recently become increasingly popular for anterior cruciate ligament reconstruction (ACLR) in the United States even though many studies have shown high allograft failure rates (Gorschewsky et al. in Am J Sports Med 33:1202, 2005; Pritchard et al. in Am J Sports Med 23:593, 2005; Roberts et al. in Am J Sports Med 19:35, 2006) and no meta-analysis or systematic review of allograft clinical stability rates in comparison to autog rafts has previously been performed. We hypothesized that allografts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
156
0
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(167 citation statements)
references
References 32 publications
3
156
0
6
Order By: Relevance
“…The first meta-analysis conducted by Prodromos et al reported better stability with autograft reconstruction [13]. However, the findings of this study were compromised by the selection bias and questionable statistical methods.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The first meta-analysis conducted by Prodromos et al reported better stability with autograft reconstruction [13]. However, the findings of this study were compromised by the selection bias and questionable statistical methods.…”
Section: Discussionmentioning
confidence: 59%
“…However, there is still considerable controversy regarding the use of allografts versus autografts in ACL reconstruction, because most of the publications are low-quality studies or different graft procurement and secondary sterilization techniques have been used in those studies. Until now, five previous studies systematically reviewed the clinical outcomes of allograft versus autograft for ACL reconstruction [13][14][15][16][17]. However, all the five systematic reviews were conducted over three years ago and the findings of those studies were compromised by the limited availability of high-quality trials.…”
Section: Introductionmentioning
confidence: 99%
“…The difference was statistically significant. Similarly, a meta-analysis (Prodromos et al, 2007) of the stability showed that irradiated grafts had an abnormal stability rate of 31% versus 12% for non-irradiated grafts, which was not to advocate the use of the irradiated allograft either, another reason against the use of irradiated allograft.…”
Section: Discussionmentioning
confidence: 99%
“…12 The results of our study with allografts are compared to certain other previous studies and tabulated (Table 4). We also compared our results with other studies where autografts were used and our results are similar to them (Table 5).…”
Section: Discussionmentioning
confidence: 98%
“…Although Gamma irradiation is known for its bactericidal and virucidal properties, a meta-analysis has shown that even a small dose of about 2 Mrad can cause about 31% abnormal laxity in ligaments reconstructed with irradiated allografts, because of alteraltion in biomechanical properties which is significantly high when compared to non-irradiated grafts which is around 12%. 12,13 Hence, all the grafts we used were maintained as fresh frozen but not irradiated. This procedure helps reduce antigenicity and disease transmission without affecting the graft strength.…”
Section: Discussionmentioning
confidence: 99%